2020
DOI: 10.1016/j.molcel.2020.09.009
|View full text |Cite
|
Sign up to set email alerts
|

A Repeat-Associated Small RNA Controls the Major Virulence Factors of Helicobacter pylori

Abstract: Highlights d A variable T stretch and NikR regulate expression of the H. pylori small RNA NikS d NikS directly represses multiple major virulence genes, such as CagA and VacA d NikS sRNA affects host cell internalization and epithelial barrier disruption d NikS is a phase-variable, global RNA regulator of virulence genes in H. pylori

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 105 publications
1
36
0
Order By: Relevance
“…Multiple binding sequences in the cagA CDS may facilitate efficient reduction of cagA transcript levels in response to HPnc4160. While the present manuscript was under revision, Eisenbart et al published a paper describing that the nickel-responsive transcriptional regulator NikR regulates the expression of HPnc4160 (which the authors of that study renamed as 'NikS'), and HPnc4160 represses multiple major virulence genes, including cagA and vacA in vitro 29 . They showed that HPnc4160 binds to the 5′UTR of the cagA mRNA of strain G27.…”
Section: Discussionmentioning
confidence: 93%
“…Multiple binding sequences in the cagA CDS may facilitate efficient reduction of cagA transcript levels in response to HPnc4160. While the present manuscript was under revision, Eisenbart et al published a paper describing that the nickel-responsive transcriptional regulator NikR regulates the expression of HPnc4160 (which the authors of that study renamed as 'NikS'), and HPnc4160 represses multiple major virulence genes, including cagA and vacA in vitro 29 . They showed that HPnc4160 binds to the 5′UTR of the cagA mRNA of strain G27.…”
Section: Discussionmentioning
confidence: 93%
“…NikS/HPnc4160, A sRNA Regulating Major Virulence Factors in H. pylori Two recent publications report the characterization of a sRNA (HPnc4160) that regulates the expression of major H. pylori virulence factors (Eisenbart et al, 2020;Kinoshita-Daitoku et al, 2021). HPnc4160 was previously identified as a highly transcribed sRNA (IsoB) expressed from the opposite strand of a poorly expressed small ORF (AapB) as a part of a probably "degenerated" type I TA system (Sharma et al, 2010;Vannini et al, 2017).…”
Section: Trans-acting Regulatory Srnas Of H Pylorimentioning
confidence: 99%
“…HPnc4160 is strongly conserved in H. pylori and harbors a length-variable T stretch upstream its −10 promoter sequence. The expression of HPnc4160 was shown to be repressed by NikR in response to nickel (Eisenbart et al, 2020) through direct binding of this transcriptional regulator to the sRNA promoter (Vannini et al, 2017). Therefore, HPnc4160 was renamed NikS (Eisenbart et al, 2020).…”
Section: Trans-acting Regulatory Srnas Of H Pylorimentioning
confidence: 99%
See 2 more Smart Citations